Reef of death - Zindel, Paul (New York : Hyperion Paperbacks for Children, 1998)
While helping a beautiful Aboriginal girl search for her people's missing treasure near the Great Barrier Reef, seventeen year-old PC finds himself fighting an evil scientist and a deadly underwater monster.
Keywords: Monsters -- Fiction; Great Barrier Reef, Old -- Fiction; Australia -- Fiction; Australian Aborigines -- Fiction; Buried treasure -- Fiction; Adventures and adventurers -- Fiction